Speaking up Behavior and Safety Climate in Saudi Public Hospitals - ALSHRAIM, Lujain; Alrashed, Abeer M (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To assess the safety climate among and between health practitioners in Saudi Arabia by identifying speaking up behavior and speaking up about the related climate. METHODOLOGY: A cross-sectional study was conducted among 135 physicians and 434 nurses in Saudi public hospitals using the Speaking Up about Patient Safety Questionnaire to assess various speaking up dimensions. Study questionnaires were completed from May to June 2019. The research purpose and confidentiality and anonymity assurance were provided at the beginning of the questionnaire. The individuals’ participation was regarded as informed consent. RESULTS: A total of 569 physicians and nurses participated. Both professions perceived concerns regarding patient safety, and nurses kept silent more yet reported a higher likelihood of speaking up than physicians. Psychological protection for speaking up was equal for both professions, but nurses reported the environment as encouraging, and physicians were more resigned. CONCLUSION: The findings of this study support further investment into research to design interventions and improve patient safety by enhancing speaking up behavior and speaking up climate through recognizing and eliminating the barriers in healthcare settings. Despite ongoing improvement efforts, the current findings highlighted that safety is yet to be fully established.